Natural history and risk factors of early respiratory responses to exposure to cotton dust in newly exposed workers - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2007)
Objective: A prospective study of newly exposed cotton workers was performed to investigate the natural history of respiratory symptoms and lung function changes. Methods: A total, of 157 workers naive to cotton dust exposure were investigated by questionnaire, spirometry, and skin tests. They were examined before employment (baseline) and at the end of the first week, and the first, third, sixth, and 12th month after starting work. Acute airway response was defined as either a cross-first-shift or a a cross-week fall in forced expiratory volume in one second (FEV1). The longitudinal change of lung function over the year was also calculated. Five hundred seventy-two personal dust sampling and 191 endotoxin measurements were performed to assess the exposure. Results: Forty percent of workers reported work-related symptoms in the first week of the study. Smoking, endotoxin, and dust concentrations were risk factors for all work-related symptoms. Acute airway responses were witnessed after immediate exposure. Female status was the only factor found to be predictive of acute airway response. The mean longitudinal fall in FEV1 at 1 year was 65.5 mL (standard error = 37.2). Age, early respiratory symptoms, and early fall in cross-week FEV1 were found to predict the 12-month fall in FEV1. Cross-first-shift and cross-week falls in M reduced in magnitude during the course of the study. Conclusions: This study Of workers naive to cotton dust exposure has demonstrated that respiratory symptoms and acute airway responses develop early following first exposure, and a tolerance effect develops in those workers with the continued exposure. Current smoking and increasing exposure predicts the development of work-related lower respiratory tract symptoms, while early symptoms and acute airway changes across the working week predict the longitudinal loss of lung function at 1 year.
Keywords: LONGITUDINAL CHANGES; HEALTH; SHIFT